If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-2)+4(x+3)=6(x+1)
We move all terms to the left:
3(x-2)+4(x+3)-(6(x+1))=0
We multiply parentheses
3x+4x-(6(x+1))-6+12=0
We calculate terms in parentheses: -(6(x+1)), so:We add all the numbers together, and all the variables
6(x+1)
We multiply parentheses
6x+6
Back to the equation:
-(6x+6)
7x-(6x+6)+6=0
We get rid of parentheses
7x-6x-6+6=0
We add all the numbers together, and all the variables
x=0
| 2h=-1 | | 5(x+4)+3x=36(x-1) | | h^2-7144.4h+921600=0 | | -3x-4=12+24 | | -4-3-9=-12+6x10 | | 3^(x-1)=28 | | 3x+18=4x-22 | | 5x+34=2(3x-7) | | 8(6x+2)=(x-2) | | X+15°+2x+15°=180° | | -30*d+5*d^2+214=234 | | 4(2x)=60-12 | | 3e/5=11 | | |3x+27|=6x | | X=0.636y-10.18 | | 6y+4=48 | | 4x+6=2.5×(x+6) | | x^-8x+9=0 | | 8=34-4x | | 4x+1=3x+9.5 | | 4+3x=9+2x | | 3(u−4)=15 | | 3n+1/4-5=2 | | 10(h+9)=260 | | 7(e+6)=63 | | 3(4x-11)=-9 | | 6^x=77 | | 20=x+(2+8)-6 | | (n+1)n=110 | | t/3=-6 | | X.2(x+3)=8-3(x-4) | | X.2(x+3)=8-3(x-4 |